SIKAP POLITIK SANG KRESNA SEBAGAI TELADAN ETIS MENGHADAPI DINAMIKA PASCA PEMILU - I Dewa Gede Darma Permana (Widya Katambung, 2025)
The holding of general elections (Pemilu) reflects political stability in a democratic country. Elections are political contests that have the potential to pose challenges. From a historical perspective, Kresna in the Mahābhārata epic is described as being able to deal with the political turmoil that occurred in the country of Bharata. Through a cultural approach, Krishna's character can be correlated with the dynamics of elections. Based on this background, three research questions are presented: The Division of Stories in the Mahabharata, Krishna's Political Stance, and Krishna's Exemplary Behavior in Facing Post-Election Dynamics. The research method used is descriptive qualitative with a historical and philosophical hermeneutic approach. Data and information sources are taken from literature studies and analyzed using the Miles and Huberman type. This research was able to describe the results that Krishna's political stance can be used as a model so that the Indonesian people can be brave, neutral, peaceful, and become smart voters in the post-election dynamics. The purpose of the research is directed as a guideline in maintaining a situation that is willing to accept the results, remain calm, and harmonious.